PERAN DAN PENTINGNYA FOSIL BAGI ILMU PENGETAHUAN - Widianto, Harry (BRIN, 2006)
One of the perceptions of the wider community regarding the meaning of a fossil in everyday life-among other things, is ancient or ancient objects. It is easier for the general public to relate the notion of fossils to something that is antique and in context of the past. Some of these perceptions are true, but in fact a fossil has a broader and more specific meaning. Therefore, the people's perception of fossils above is only an initial understanding - a part of the whole understanding - which is still far from the real understanding of a fossil, so it must be equipped with more perfect definitions. In the above context, this paper will try to provide some understanding of fossils and their details, so that people's perceptions of the inappropriate understanding of fossils can be avoided.